International Business in the Information and Digital Age. - van Tulder, Rob. (Progress in International Business Research Ser., 2018)
The information and digital age is shaped by a smallnumber of multinational enterprises from a limited number of countries. Thisvolume covers the latest insight from the International Business discipline onprevailing trends in business model evolution. It also discusses criticalissues of regulation in the new information and digital space..